2020
DOI: 10.3390/molecules25112472
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Brain Network Research in Alzheimer’s Disease Using Persistent Features

Abstract: Despite the severe social burden caused by Alzheimer’s disease (AD), no drug than can change the disease progression has been identified yet. The structural brain network research provides an opportunity to understand physiological deterioration caused by AD and its precursor, mild cognitive impairment (MCI). Recently, persistent homology has been used to study brain network dynamics and characterize the global network organization. However, it is unclear how these parameters reflect changes in structural brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
(91 reference statements)
1
9
0
Order By: Relevance
“…In our prior study on AD brain networks ( Kuang et al, 2019a ), we have proposed an integrated persistent feature (IPF) based on persistent homology that achieves holistic descriptions of spatial dynamics of the brain network. We have also found that the IPF is more robustness than graph theory-based metrics in our prior studies ( Kuang et al, 2019a , b , 2020a , b ). However, all existing studies on persistent homology only focus on the feature invariants in the process of spatial dynamics, but no literature studies have reported the influence of the change of time window on feature invariants.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…In our prior study on AD brain networks ( Kuang et al, 2019a ), we have proposed an integrated persistent feature (IPF) based on persistent homology that achieves holistic descriptions of spatial dynamics of the brain network. We have also found that the IPF is more robustness than graph theory-based metrics in our prior studies ( Kuang et al, 2019a , b , 2020a , b ). However, all existing studies on persistent homology only focus on the feature invariants in the process of spatial dynamics, but no literature studies have reported the influence of the change of time window on feature invariants.…”
Section: Introductionsupporting
confidence: 63%
“…Because IPF is a monotonically decreasing convergence function, the slope of IPF (SIP) is used as an index to quantify the dynamic research of AD brain network. We have successfully applied the SIP to AD brain network analysis in our prior studies ( Kuang et al, 2019a , b , 2020a , b ). Our opensource code of persistent homology can be downloaded at http://gsl.lab.asu.edu/software/IPF .…”
Section: Methodsmentioning
confidence: 99%
“…The network is comprised of information of relations or interconnections that link many elements in the neurobiological system. The neurons of the human brain are interconnected through synaptic connections and anatomical projections mediate the communication among brain areas, forming a highly complex network system in human beings (Bassett and Sporns, 2017 ; Kuang et al, 2020 ). Structural network analysis based on DTI is a newly-developed method to reflect the topological structural alterations and the connectivity of the brain structural network (Bassett et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The topological features have been well defined, such as small-worldness [ 21 23 ], global and local efficiency [ 24 ], and highly connected hubs [ 25 ], which contain node degree, node betweenness, and so on. The brain network features have been characterized in AD [ 26 , 27 ], schizophrenia [ 28 ], multiple sclerosis [ 29 ], and other conditions. Moreover, several analyses have indicated that patients with PACG exhibit signs of changes in brain network properties that were identified in previous resting-state fMRI studies.…”
Section: Introductionmentioning
confidence: 99%